Postoperative Management of Lung Transplant Recipients in the Intensive Care Unit. (15th December 2021) - Di Nardo, Matteo; Tikkanen, Jussi; Husain, Shahid; Singer, Lianne G.; Cypel, Marcelo; Ferguson, Niall D.; Keshavjee, Shaf; Del Sorbo, Lorenzo
Abstract : The number of lung transplantations is progressively increasing worldwide, providing new challenges to interprofessional teams and the intensive care units. The outcome of lung transplantation recipients is critically affected by a complex interplay of particular pathophysiologic conditions and risk factors, knowledge of which is fundamental to appropriately manage these patients during the early postoperative course. As high-grade evidence-based guidelines are not available, the authors aimed to provide an updated review of the postoperative management of lung transplantation recipients in the intensive care unit, which addresses six main areas: (1) management of mechanical ventilation, (2) fluid and hemodynamic management, (3) immunosuppressive therapies, (4) prevention and management of neurologic complications, (5) antimicrobial therapy, and (6) management of nutritional support and abdominal complications. The integrated care provided by a dedicated multidisciplinary team is key to optimize the complex postoperative management of lung transplantation recipients in the intensive care unit. Abstract : The outcome of lung transplant recipients is critically affected by a complex interplay of particular pathophysiologic conditions and risk factors, knowledge of which is fundamental for the appropriate postoperative management of these patients in the intensive care unit.